Thermohydraulic analysis of hybrid nanofluid in a multilayered copper foam heat sink employing local thermal non-equilibrium condition: Optimization of layers thickness. (25th November 2020) - Ghaneifar, Milad; Arasteh, Hossein; Mashayekhi, Ramin; Rahbari, Alireza; Babaei Mahani, Roohollah; Talebizadehsardari, Pouyan
Highlights: Study multi-layered copper foam heat sink with different thicknesses. Thermohydraulic analysis of water-graphene nanoplatelet/platinum hybrid nanofluid. Using thermal non-equilibrium model for nanofluid flow in porous medium. Optimization of particle diameters and porosities of the porous medium. 145% and 191% higher heat transfer for constant porosity and particle diameter modes. Abstract: In the present study, fluid flow and heat transfer characteristics of a heat sink partially fitted with multilayered porous medium are analyzed. The multilayered copper foam contains three different layers placed at the bottom wall of the heat sink exposing to a uniform heat flux. The whole occupied volume of the porous region is 60% of the channel. The main objective of the current study is to reveal a layout for the porous medium with optimum thickness for each layer in two proposed models to maximize the heat transfer and minimize the pressure drop. In the constant particle diameter model, all three layers have an equal particle diameter of 1.5 cm with three porosities of 0.95, 0.85 and 0.75 from bottom to top. In the constant porosity model, all three layers have an equal porosity of 0.95 with three particle diameters of 0.5, 1 and 1.5 cm from bottom to top. To trade-off between the desirable (heat transfer) and undesirable (pressure drop) outcomes, the dimensionless number of performance evaluation criterion (PEC) is determined. Darcy–Brinkman–Forchheimer and local thermal non-equilibrium (LTNE) models are applied to solve the governing equations in the porous region. The CFD numerical simulations are conducted to analyze the effect of each layer thickness of the multilayered porous medium in the two proposed models on the thermohydraulic parameters such as friction coefficient, Nusselt number and PEC number. At the optimum layouts of the porous medium, water-graphene nanoplatelet/platinum hybrid nanofluid is applied to enhance the thermal performance of the heat sink. The obtained results reveal that the highest PEC number is achieved in the constant porosity model equal to 1.17 at the case in which the lower, middle and upper metal foam layer thicknesses are 0.6, 1 and 0.2 cm, respectively, resulting in 145% heat transfer enhancement. In constant particle diameter model, the highest PEC number equals to 1.26 at the case in which the lower, middle and upper metal foam layer thicknesses are 1, 0.6 and 0.2 cm, respectively, resulting in 191% heat transfer augmentation compared with the plain channel. Further increase in PEC number is observed by adding nanoparticles to the base fluid for nanofluid volume concentration of 0.1% in constant porosity and particle diameter models which are equal to 1.22 and 1.31, respectively.